The use of digital and imaging technology for students’ evaluation in simulation operative technique - Al-Marzok, Maan Ibrahim; Abdul Majeed, Kais Raad; Junaidi, Mohamad Termidzi (2009)
Objectives: To evaluate the efficacy of using digital and imaging technology in the assessment of students in the simulation operative technique. Methods: 47 students in the kulliyyah of dentistry/International Islamic University Malaysia was examined for Class II cavity preparation for amalgam on plastic tooth number 46. The evaluation was done by two faculty members using the digital and imaging technology acronym as "DIET" (Dental Instruction, Evaluation and Training System). Results were compared with marks obtained by direct visual assessments. Fifteen percent of the preparations were reevaluated to determine intra-examiner reliability. The evaluations also were analyzed for inter-examiner reliability. Results: The results taken through the use of the digital and imaging system was found to have no significant difference with those obtained from the direct visual assessment. Conclusion: The use of the new digital and imaging technology is helpful to facilitate web-based teaching and assist Dental faculties’ members in the grading of dental students. This would allow Malaysian dental faculties to be in the league of globally-known dental faculties which are using similar solutions. The use of the system has several advantages over the traditional method. It frees the lecturers from the paperwork and reduces the direct contact with students allowing lecturers to evaluate all aspects of the procedure at any time. This also decrease or eliminate students’ need to wait “in line” for evaluation. Limitation of contact with patients may reduce the cross-infection.